Biomechanical analysis of the waterpolo delay shot - Ball, K. (Proceedings of the First Australasian Biomechanics Conference, 1996, Sydney, 1996)
The purpose of this study was to compare the delay shot with a shot for maximal speed (termed 'fast shot' for this study) to assess the key biomechanical and coaching factors of the shot. The major role of the delay shot is one of deception. This deception is primarily developed by maintaining a fairly similar forward swing to a fast shot, but slowing it down to generate the illusion that the opportunity to shoot has passed. The forward swing from the end of the delay to release must be performed rapidly to take advantage of this deception. The fast shot exhibits the more classical throwing technique where most speed is generated from trunk rotation. In the delay shot, reduced shoulder range and angular velocity suggest that trunk contribution is limited. Internal rotation at the shoulder assumes a far greater role in developing ball speed than during a fast shot. Horizontal adduction may also be a major speed generator. The 50 Hz sample rate was a limitation of this study, as was the small subject numbers. The ability to produce a 'full body' image of the athlete may be useful in further qualitative and quantitative studies. (from: Proceedings of the First Australian Biomechanics Conference; ISBN 0 86758 999 X)